Multiple Dural Arteriovenous Shunts in a 5-Year-Old Boy - Ushikoshi, Satoshi; Kikuchi, Yoichi; Miyasaka, Kazuo (American Journal of Neuroradiology, 1999)
Summary: We describe a rare case of multiple dural arteriovenous shunts (DAVSs) in a 5-year-old boy. MR imaging performed at 1 year of age showed only a dilated anterior part of the superior sagittal sinus; however, angiography at 5 years of age revealed an infantile-type DAVS there and two other DAVSs of the adult type. The pathophysiological evolution of DAVSs in children and their treatment strategies are discussed.